"In Africa, There Was No Family Planning. Every Year You Just Give Birth": Family Planning Knowledge, Attitudes, and Practices Among Somali and Congolese Refugee Women After Resettlement to the United States. (February 2020) - Royer, Pamela A.; Olson, Lenora M.; Jackson, Brandi; Weber, Lana S.; Gawron, Lori; Sanders, Jessica N.; Turok, David K.
It is crucial for refugee service providers to understand the family planning knowledge, attitudes, and practices of refugee women following third country resettlement. Using an ethnographic approach rooted in Reproductive Justice, we conducted six focus groups that included 66 resettled Somali and Congolese women in a western United States (US) metropolitan area. We analyzed data using modified grounded theory. Three themes emerged within the family planning domain: (a) concepts of family, (b) fertility management, and (c) unintended pregnancy. We contextualized these themes within existing frameworks for refugee cultural transition under the analytic paradigms of "pronatalism and stable versus evolving family structure" and "active versus passive engagement with family planning." Provision of just and equitable family planning care to resettled refugee women requires understanding cultural relativism, social determinants of health, and how lived experiences influence family planning conceptualization. We suggest a counseling approach and provider practice recommendations based on our study findings.